A Novel Bisretinoid of Retina Is an Adduct on Glycerophosphoethanolamine - Yamamoto, Kazunori (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. Fluorescent bisretinoid compounds accumulate in retinal pigment epithelial (RPE) cells as a consequence of two processes: random reactions of vitamin A aldehyde in photoreceptor cell outer segments, and phagocytosis of discarded photoreceptor outer segment discs by RPE. The formation of bisretinoid is accentuated in some forms of retinal degeneration. The detection of a novel bisretinoid fluorophore that is a conjugate of all-trans-retinal and glycerophosphoethanolamine is reported. METHODS. Human RPE/choroid, eyes harvested from Abca4 (ATP-binding cassette transporter 4) null mutant mice, and biosynthetic reaction mixtures were analyzed by ultra performance liquid chromatography coupled to mass spectrometry and by nuclear magnetic resonance spectra and spectrofluorometry. RESULTS. A fluorescent compound in mouse eyes and in human RPE/choroid corresponded to the product of the reaction between all-trans-retinal and glycerophosphoethanolamine (A2-GPE), as determined on the basis of molecular weight (m/z 746), absorbance (approximately 338,443 nm), and retention time. Nuclear magnetic resonance spectra were consistent with a pyridinium molecule with a glycerophosphate moiety. The emission maximum of A2-GPE was approximately 610 nm. A2-GPE accumulated with age in mouse eyes and was more abundant in Abca4(−/−) mice, a model of recessive Stargardt disease. CONCLUSIONS. To date, several bisretinoids of RPE lipofuscin have been isolated and characterized, and for all of these, formation involves the membrane phospholipid phosphatidylethanolamine. Conversely, the bisretinoid A2-GPE is detected as sn-glycero-3-phosphoethanolamine (GPE) derivatized by two all-trans-retinal. The pathways by which A2-GPE may form under conditions of increased availability of all-trans-retinal, for instance in the Abca4(−/−) mouse, are discussed.